2020
DOI: 10.24106/kefdergi.3593
|View full text |Cite
|
Sign up to set email alerts
|

Polislerin Hayat Boyu Öğrenme Eğilimlerinin İncelenmesi

Abstract: Bu araştırmanın amacı, polis memurlarının hayat boyu öğrenme eğilimlerini incelemek ve bazı demografik değişkenlerle ilişkilerini ortaya koymaktır. Araştırmanın evrenini 2018 yılında Gaziantep ili Şahinbey ve Şehitkamil İlçesi Emniyet Müdürlüklerinde görevli polis memurları oluşturmaktadır. Çalışmanın örneklemini ise farklı birimlerde görev yapan rasgele seçilen 304 polis memuru oluşturmaktadır. Bu araştırma belirli bir grubun özelliklerini ortaya koymak için yapıldığından bir tarama araştırmasıdır. Araştırmad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…However, there is a significant difference in favor of women in terms of the lack of self-regulation, the lack of curiosity sub-dimensions and the total score of the teacher candidates in their lifelong learning levels according to gender. Besides; there are also studies (Bulaç & Kurt, 2019;Çam, 2017;Diker-Coşkun & Demirel, 2012;Orhan, 2023;Yaman & Yazar, 2015) that find thatLLTof teachers are affected by the gender variable and create a significant difference in favor of female teacher candidates. Also, it is found that the average scores of female teachers" LLT were significantly higher than the average scores of male teachers in the perseverance dimension (Tanatar, 2017); in the incentive and perseverance dimensions (Kabal, 2019); and in the incentive, perseverance and deprivation in regulating learning dimensions (Aydın, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a significant difference in favor of women in terms of the lack of self-regulation, the lack of curiosity sub-dimensions and the total score of the teacher candidates in their lifelong learning levels according to gender. Besides; there are also studies (Bulaç & Kurt, 2019;Çam, 2017;Diker-Coşkun & Demirel, 2012;Orhan, 2023;Yaman & Yazar, 2015) that find thatLLTof teachers are affected by the gender variable and create a significant difference in favor of female teacher candidates. Also, it is found that the average scores of female teachers" LLT were significantly higher than the average scores of male teachers in the perseverance dimension (Tanatar, 2017); in the incentive and perseverance dimensions (Kabal, 2019); and in the incentive, perseverance and deprivation in regulating learning dimensions (Aydın, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Literatürde bu çalışmayı destekler nitelikte yaşam boyu öğrenmenin cinsiyet değişkenine göre anlamlı düzeyde farklılaştığını ve yaşam boyu öğrenme eğilimlerinin kadınlarda anlamlı düzeyde daha yüksek olduğunu belirten çalışmalar bulunmaktadır (Çetinkaya vd., 2019;Dervişoğulları vd., 2016;Diker Coşkun & Demirel, 2012;Gökyer & Türkoğlu, 2019;Yılmaz vd., 2014;Horuz, 2017;Ayra, 2015;Gür Erdoğan, 2014;Karaduman, 2015;Özçiftçi, 2014;Kılıç & Tuncel Ayvaz, 2014;Kılınç & Yenen, 2015;Akcaalan & Arslan, 2016;Kılıç, 2015;Diker Coşkun, 2009;Sucu, 2017;Kurt vd., 2019;Aydın, 2018;Karaman & Aydoğmuş, 2018;Akyol vd., 2018;Gencel, 2013;İzci & Koç, 2012). Bununla birlikte Dindar ve Bayraktar (2015), Dündar (2016), Tunca vd., (2015, Yaman (2015), Yıldırım (2015), Özçiftçi (2014), Yasa (2018), Oral ve Yazar (2015), Şahin, vd., (2010), Yaman ve Yazar, (2015) ve Yılmaz (2016) da yaptıkları çalışmalarda cinsiyetin yaşam boyu öğrenmeye anlamlı bir etkisinin olmadığını belirtmektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Yine literatürde cinsiyet değişkeni ile dijital okuryazarlık arasında anlamlı farkın ortaya çıkmadığı çalışmalar da mevcuttur (Arık ve Bektaş, 2016;Kara, 2021;Danner ve Pessu, 2013;Hargittai ve Shafer, 2006;Sarıkaya, 2019). Diğer taraftan yaşam boyu öğrenme eğilimi ile cinsiyet değişkenine ilişkin literatür incelendiğinde anlamlı farkın ortaya çıkmadığı pek çok çalışma mevcuttur (Duymuş ve Sulak, 2018;Güzel, 2017;Kangalgil ve Özgül 2018;Saylam vd., 2019;Yaman ve Yazar, 2015).…”
Section: Tartişma Ve Sonuçunclassified